'Lipase and protease production of dairy Penicillium sp. on milk‐protein‐based solid substrates'. (26th April 2019) - Kumura, Haruto; Satoh, Megumi; Machiya, Taiki; Hosono, Makoto; Hayakawa, Toru; Wakamatsu, Jun‐ichi
Abstract : The lipolytic and proteolytic activity of Penicillium camemberti PC TT033 and Penicillium roqueforti PR G3, cultured on the whey solids or simulated cheese media, were compared under several pH reaction conditions. Lipolytic activity was higher when both strains had been cultured on the whey medium than on the simulated cheese medium, whereas proteolytic activity was less influenced by the culture medium. The relationship between the reaction pH and these enzyme activities was dependent on the culture medium, which suggested that the expression level and balance of isozyme rely on the culture substrate.